Estimating the number of airports potentially contaminated with perfluoroalkyl and polyfluoroalkyl substances from aqueous film forming foam: A Canadian example. (15th September 2018) - Milley, Shawn A.; Koch, Iris; Fortin, Patricia; Archer, Jeremy; Reynolds, David; Weber, Kela P.
Abstract: Assessing the extent to which emerging contaminants (ECs) such as perfluoroalkyl and polyfluoroalkyl substances (PFAS) have been released into the environment is one of the foundations for developing effective management and remediation strategies for impacted sites. PFAS are known to have caused the contamination of soil, groundwater, and surface water as a result of aqueous film forming foam (AFFF) being accidentally or intentionally released into the environment. To date, the scope of the issue has not been evaluated in Canada. In this study we developed a framework, in the form of a decision tree, to estimate the number of potentially PFAS impacted airport sites in Canada as a result of AFFF releases. The screening process was completed using publicly available resources including airport websites, the Canadian Owners and Pilots Association website, Sky Vector, Transport Safety Board of Canada aviation investigation reports, the Aviation Safety Network website, and Google maps. The methodology presented in this study could be used to identify additional PFAS impacted sites in Canada or other jurisdictions worldwide. 2071 airport/heliport sites in Canada were investigated with indications that 152 (7%) of these sites likely have PFAS contamination as a result of the use of AFFF at firefighter training areas (FFTAs) and/or accidents where fires occurred. In addition, another 268 sites (13%) were identified as possibly impacted with PFASs primarily as a result of the location having the ability to store and dispense petroleum products, and therefore having AFFF systems onsite. Surficial geology was also identified for all sites determined to likely have PFAS contamination. An estimated 42.8% had surficial geology composed of sand, 27% had clay, 19.7% organic-based, with the remaining sites found on cryosols or rock. Methodological validation was also completed. The procedure used in this study successfully predicted occurrences of PFAS contamination at 25 sites where contamination, as a result of AFFF use, was confirmed by Canadian governmental departments. For these 25 sites, the distance from potential release areas to the nearest surface water was calculated. Five of the sites were within 200 meters of surface water, 19 were within one kilometer, and all 25 were within 2.5 kilometers. This suggests that surface water may have been historically impacted by PFAS at as many as 152 to 420 different airport locations in Canada. Highlights: Decision tree developed and used to identify PFAS contaminated airports in Canada. Of the 2071 airports in Canada, 152 are likely contaminated with PFAS. Of the likely contaminated sites 43% and 27% had surficial sand and clay respectively. Surface waters may be impacted near 152 to 420 airport sites in Canada. Data can be used to develop a prioritization framework for management purposes.